Dampak Fiskal Pembangunan Kawasan TOD Karawang Terhadap APBD Pemerintah Daerah Kabupaten Karawang - Nudi G Subagja; zefri; Irwan Prasetyo (Journal of Urban and Regional Development Studies, 2024)
The existence of the Jakarta-Bandung High-Speed Train Project (KCIC), which is planned to have a station in Karawang Regency, has spurred the development of a transit-oriented development (TOD) area. The development of this area will impact the provision of supporting facilities and infrastructure such as housing, healthcare facilities, educational facilities, and others. The Karawang TOD area, covering an area of approximately ±250 hectares, is located in two villages, namely Wanasari and Wanakerta, in the Telukjambe Barat District of Karawang Regency, West Java Province. The development of the Karawang TOD area will have both positive and negative effects on local government finances. Revenue from development comes from taxes, levies, and balance funds. Meanwhile, local government expenditures are incurred for the provision and maintenance of public infrastructure due to development. This study discusses the extent to which the development of the Karawang TOD area affects local government finances. The method used is fiscal impact analysis. Calculations are only made for revenue and expenditure that are direct impacts of the development of the Karawang TOD area. Based on fiscal impact analysis in this study (2019-2043), the development of the Karawang TOD area has a positive value of Rp. 316,495,375,189,-. This means that local government revenue exceeds expenditure (surplus). The positive result is attributed to the efforts made by the developers to internalize the impacts arising from development. A positive result also implies that the development of the Karawang TOD area does not burden the local government budget, and therefore, development can continue until completion according to the planned schedule. However, it is known from the analysis that there is a significant decrease after the completion of the development of the Karawang TOD area, assuming that the entire area is fully operational. Therefore, a fiscal impact analysis with a longer time frame is needed to ensure that new developments do not have a negative impact on local government finances. Considering the importance of understanding the fiscal impact of new development, fiscal impact analysis can be used as a procedure in the formulation of new development policies by local governments